PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 009 TELUK NILAP KECAMATAN KUBU KABUPATEN ROKAN HILIR - Suryanti '; Zulkifli '; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was conductedbecause of the low IPA students' learningoutcomes, with an average value of 62.9 class. While the value of minimumcompleteness criteria (KKM) IPA 65. This research is a classroom actionresearch (CAR). Conducted aiming to improve science learning outcomes fifthgrade students of SDN 009 Gulf Nilap Kubu district of Rokan Hilir. Formulationof the problem: Is Application Type STAD Cooperative Learning Model canimprove science learning outcomes fifth grade students of SDN 009 Gulf NilapKubu district of Rokan Hilir. The student learning outcomes of prior actions by anaverage of 62.9. Student learning outcomes improved after action by an averageof 70%, while in the second cycle increased by an average of 83%. So improvingstudent learning outcomes of basic score kesiklus an increase of 7.1% from thebase score kesiklus while two increased to 20.1%. While the activities of studentsin the first cycle with an average of 66.66% in the second cycle on average by81.24%. While the activity of the teacher on the first cycle with an average of72.91% in the second cycle reaches 85.41%. These results prove that theimplementation of STAD cooperative learning model to improve learningoutcomes IPA 009 fifth grade students of SDN Gulf Nilap Kubu district RokanHilir.Keywords: Cooperative Type STAD, Science leaning outcome